MT-CHR: A modified threshold-based cluster head replacement protocol for wireless sensor networks. (November 2018) - Darabkh, Khalid A.; Al-Rawashdeh, Wala'a S.; Hawa, Mohammed; Saifan, Ramzi
Abstract: The Threshold-based Low-energy Adaptive Clustering Hierarchy (T-LEACH) protocol declares that cluster heads do not have to turn over every round but rather every batch of rounds. In other words, nodes keep serving as cluster heads as long as their energy is higher than a threshold energy. This article imposes upon major drawbacks of T-LEACH protocol and presents a Modified Threshold-based Cluster Head Replacement (MT-CHR) protocol. In the MT-CHR protocol, a new probability of being a cluster head, for any node in any round, has been proposed which agrees fairly with the assumptions introduced in LEACH protocol. Moreover, a new expression for threshold energy is proposed in which delaying the first node death and avoiding any data loss are taken into consideration. The performance of MT-CHR is evaluated using alive nodes, network lifetime, as well as network utilization performance metrics. The results are further compared with those obtained importantly from LEACH and T-LEACH protocols and the contributions of MT-CHR protocol are extremely impressive. As far as the real sensor network is concerned, the MT-CHR protocol is highly applicable and very effective as long-lasting networks are ascertained.